ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 PEGAWAI TETAP PADA PT. BANK RAKYAT INDONESIA KANTOR - Baguna, Nabella L; Pangemanan, Sifrid S.; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Income Tax Article 21 is tax payableon income which becomes the obligation of Taxpayer to pay it. Such income is in the form salaries, honoraria, allowances and other payment of any kind in respect of employment, services or activities performed by an individual Taxpayer in the country. The law used to regulate the amount of tax rqate, the procedure of payment and tax reporting is an Act No. 36 of 2008. The purpose of this study is to find out how the Calculation and Reporting Income Tax Article 21 At PT. Bank Rakyat Indonesia Branch Manado. Method of analysis used in thes research is decriptive method is to discuss of the problem by collection, decompile, calculate, compare, and explain a situation so that it can be drawn conclusions that include calculation and reporting Article 32 of permanent employees at PT. Bank Rakyat Indonesia Branch Manado. Based on the result of the study found the there is a mistake in the Calculation of Income Tax Article 21 at PT. Bank Rakyat Indonesia Branch Manado, resulting in the overpayment resulting in taxpayer incur losses.Keywords: Accounting, Income Tax Article 21